The Antigen of Anti-neutrophil Antibodies in Patients with Copper Deficiency and Neutropenia is Fy.GAMMA. receptor III - 樋口 重典; 直江 弘昭; HIRASHIMA Mitsuomi; MATSUDA Ichiro (Japanese Journal of National Medical Services, 1995)
Using the human peripheral blood normal neutrophils and the promyelocytic leukemia cell line (HL-60), the antigen of anti-neutrophil antibodies (ANA) in patients with copper deficiency was investigated. These patients were classified as group A and group B; Group A was ANA positive with neutropenia while group B was ANA positive without neutropenia. 1) The serum containing ANA from group A showed low binding (0-6.1%) to HL-60 cells, but that from group B bound to HL-60 (64.2-87%). 2) Induced differentiation of HL-60 by DMSO enhanced expression of CD 16 and CD 11b. The binding of ANA from group A patients to differentiated HL-60 was increasd (10.0-14.6%). 3) The monoclonal antibody of CD 16 showed the inhibition of ANA binding of group A to the peripheral neutrophils, but not that of group B. These data suggested that ANA in patients with copper deficiency and neutropenia were recognizing Fcγ receptor III as antigen. 鋼欠乏症にみられる抗好中球抗体(ANA)の認識抗原について, 好中球および前骨髄性白血病細胞(HL-60)を用いて検討した. ANA陽性で好中球減少のある患者をA群, ANA陽性だが好中球減少のない患者をB群とした. 1) A群の抗体はHL-60に付着しなかったが, B群の抗体は付着した. 2) 分化したHL-60ではA群の抗体の付着率の増加がみられた. 3) 分化したHL-60ではCD16, CD11bの抗原が発現していた. 4) CD16によりA群の抗好中球抗体の付着は阻止されたが, B群の抗体の付着は阻止されなかった. 以上より, 銅欠乏症で好中球減少をきたす患者の抗好中球抗体はFcγレセプターIIIを認識することが判明した.